2007
DOI: 10.1186/1477-7800-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Venous gangrene and cancer: A cool look at a burning issue

Abstract: Venous gangrene (VG) is defined as a clinical triad of skin necrosis and discolouration, documented evidence of venous thromboembolism (VTE) and presence of palpable or doppler-identifiable arterial pulsation. Venous gangrene is rare condition which is associated with poor prognosis in cancer patients. The pathogenesis of VG is multifactorial and could paradoxically be due to warfarin treatment. Heparin Induced Thrombocytopenia (HIT) associated venous gangrene develops when heparin therapy is discontinued and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In these patients there is direct activation of their clotting system by cancer cells, and indirectly by activation of platelets, monocytes and endothelial cells. Cytokines such as tumor necrosis factor-α and interleukin-1β released by tumor cells activate the tissue factor (TF) [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these patients there is direct activation of their clotting system by cancer cells, and indirectly by activation of platelets, monocytes and endothelial cells. Cytokines such as tumor necrosis factor-α and interleukin-1β released by tumor cells activate the tissue factor (TF) [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that a supratherapeutic INR (≥6.0), warfarin-induced PC and protein S deficiency, obesity, and metabolic syndrome were among several factors to predispose to venous thrombosis and gangrene in patients with cancer [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In advanced cases, it is marked by severe venous hypertension with collateral and microvascular thrombosis, leading to venous gangrene. Venous gangrene is particularly associated with warfarin-mediated protein C depletion in patients with cancer or heparin-induced thrombocytopenia [ 8 , 9 ].…”
Section: Contentsmentioning
confidence: 99%
“…In advanced cases, it is marked by severe venous hypertension with collateral and microvascular thrombosis, leading to venous gangrene. Venous gangrene is particularly associated with warfarinmediated protein C depletion in patients with cancer or heparin-induced thrombocytopenia [8,9].…”
Section: ) Symptomsmentioning
confidence: 99%